Peramalan Utilisasi Perangkat Jaringan dan Bandwidth Dengan Metode Holt-Winters dan Multi Layer Perceptron - Muhammad Taufiq; Dedy Sugiarto; Abdul Rochman (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2020)
Network devices become an important medium for transferring data from one node to another node in the form of switches, routers or network security devices. The reliability of network devices must be maintained both in terms of device resources and bandwidth. The study was conducted by applying the Holt-Winters and Multi Layer Perceptron (MLP) method to network device and bandwidth data utilization. The two methods are compared to assess which accuracy is better when applied to network device and bandwidth utilization data by calculating Root Mean Squared Error (RMSE) and Mean Absolute Percentage (MAPE). The results of the measurement of accuracy in the network device testing data, MLP produces a value of RMSE of 5,67 and MAPE of ​​2.34, and Holt-Winters produces a value of RMSE of ​​14.56 and MAPE of 2.95. For the results of the measurement of accuracy in the bandwidth testing data with MLP produces a value of RMSE of ​​0.13 and MAPE of ​​ 7.27, and Holt-Winters produces RMSE values of ​​2.59 and MAPE of 134.31. Based on the results of these measurements it is concluded that the MLP method has a smaller error value compared to the Holt-Winters method applied to network device and bandwidth utilization data with a span of 3 years historical data.